2017
DOI: 10.1371/journal.pone.0169277
|View full text |Cite
|
Sign up to set email alerts
|

Diet and ADHD, Reviewing the Evidence: A Systematic Review of Meta-Analyses of Double-Blind Placebo-Controlled Trials Evaluating the Efficacy of Diet Interventions on the Behavior of Children with ADHD

Abstract: IntroductionAttention-deficit/hyperactivity disorder (ADHD) is a debilitating mental health problem hampering the child’s development. The underlying causes include both genetic and environmental factors and may differ between individuals. The efficacy of diet treatments in ADHD was recently evaluated in three reviews, reporting divergent and confusing conclusions based on heterogeneous studies and subjects. To address this inconsistency we conducted a systematic review of meta-analyses of double-blind placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 123 publications
2
82
0
4
Order By: Relevance
“…In a small sample of obese women, nondepressed elderly women consumed more CHOs than those who were depressed (101,102). Depressed individuals in a small Turkish study consumed 55% of "research is required for AFC (artificial food color) elimination before advising this intervention as ADHD treatment" for children (75).…”
Section: Grains Chos Glycemic Index and Glycemic Loadmentioning
confidence: 99%
“…In a small sample of obese women, nondepressed elderly women consumed more CHOs than those who were depressed (101,102). Depressed individuals in a small Turkish study consumed 55% of "research is required for AFC (artificial food color) elimination before advising this intervention as ADHD treatment" for children (75).…”
Section: Grains Chos Glycemic Index and Glycemic Loadmentioning
confidence: 99%
“…In a small sample of obese women, nondepressed elderly women consumed more CHOs than those who were depressed (101,102). Depressed individuals in a small Turkish study consumed 55% of "research is required for AFC (artificial food color) elimination before advising this intervention as ADHD treatment" for children (75).…”
Section: Grains Chos Glycemic Index and Glycemic Loadmentioning
confidence: 99%
“…Although these dietary interventions for managing ADHD have been proposed by practitioners of both Western and traditional Chinese medicine, limited research exists on the efficacy and safety of dietary intervention as an adjunct to conventional medications (40,49,(76)(77)(78)(79). To date, findings suggest elimination diets and fish oil supplementation may hold promise in certain cases (40,75,76) and may offer treatment opportunities for subgroups of children with ADHD who do not respond to or are too young for medication (75).…”
Section: Diet and Treatment Of Adhdmentioning
confidence: 99%
“…Since blood levels of docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and arachidonic acid (AA) have been found to be significantly decreased in children with ADHD compared to controls, numerous clinical studies have examined the effects of omega-3 PUFA supplementation on ADHD symptoms. A systematic review of meta-analyses of double-blind placebo-controlled trials, in which ADHD symptoms were rated by parents and teachers, concluded that the effect sizes for PUFA supplementation were small (19). The pooling of the negative results of a more recent study with previous findings showed no overall effect of omega-3 PUFAs on…”
mentioning
confidence: 99%
“…The role of food hypersensitivities in ADHD is a promising avenue worthy of further exploration. A systematic review of metaanalyses of double-blind placebo-controlled trials found no convincing evidence of therapeutic efficacy of artificial food color elimination, while the few-foods diet, which excludes many foods and additives, may offer new treatment options (19). The hypothesis of a relationship between food hypersensitivity and ADHD is supported by several studies (44)(45)(46)(47)(48).…”
mentioning
confidence: 99%